Advanced Left Atrial Remodeling and Appendage Contractile Dysfunction in Women Than in Men Among the Patients With Atrial Fibrillation: Potential Mechanism for Stroke. Issue 7 (July 2016) - Yu, Hee Tae; Lee, Jihei Sara; Kim, Tae‐Hoon; Uhm, Jae‐Sun; Joung, Boyoung; Hong, Geu‐Ru; Lee, Moon‐Hyoung; Shim, Chi Young; Pak, Hui‐Nam
Abstract : Background: The risk of stroke imposed by atrial fibrillation (AF) is significantly greater in women than men; however, the mechanism remains elusive. We hypothesized that left atrial (LA) remodeling and poor contractile function of LA appendage (LAA) would be more predominant in women than men among AF patients. Methods and Results: A total of 579 AF patients (216 women vs age‐, AF type–, and incidences of heart failure, hypertension, diabetes mellitus, stroke or transient ischemic attack, and vascular disease–matched 363 men, 61.3±10.2 years old, 70.1% paroxysmal AF) who underwent AF catheter ablation were included. Sex differences in LA volume index (LAVI) and LAA emptying flow velocity (FV) were analyzed in risk factor 0, 1, and ≥2 groups, according to their CHA2 DS2 ‐VASc scores beyond sex category. LAA‐FV was more significantly reduced in women with risk factor ≥2 than in men of the same risk group ( P =0.022). Women showed greater LAVI than their male counterparts in the risk factor ≥2 group ( P <0.001). The majority of female patients with a history of stroke had a large LAVI and low LAA‐FV ( P <0.001); however, no such distribution was observed in men ( P =0.596). LA volume index (odds ratio [OR], 1.038; 95% CI, 1.003–1.075, P =0.035) or LAA‐FV (OR, 0.976; 95% CI, 0.952–0.999; P =0.047) was significantly associated with a history of stroke in women. Conclusions: More‐extensive LA remodeling and deterioration in LAA function were noted in women than in men with high calculated risk of stroke in AF.